Grand Design Pembangunan Nasional (Skenario Sufi Indonesia) - Nataatmaja, Hidayat (Unisia, 2016)
We have to find the prime causa that pushed us into the inside of the ugliest hell-crisis, the only way to find the way out. It could not be free market as it is only an accomplish; it could not be corruption as it was only an ugly effect. Only a Sufi Master can see the true prima causa of the holocaust: SCIENCE! There is only one way to go, for Indonesia and for the world, namely to trigger the Millennium Scientific Revolution: (i) Merging quantum and relativity physics into the expanded quantum theory to kill Schroedinger's Cat dead; (ii) open the Holy Quran and read the most precious thing hidden inside, Spiritual Intelligence of man! World crises shall finally evaporate to nothing, terrorism included! Not only terrorism of the weak against the strong, but also terrorism of the strong against the weak.